PTH-140 Virtual reality simulation training in gastrointestinal endoscopy: a cochrane systematic review. (8th June 2018) - Plahouras, Joanne; Khan, Rishad; Johnston, Bradley C; Scaffidi, Michael A; Grover, Samir C; Walsh, Catharine M
Abstract : Introduction: Endoscopy simulation is increasingly being integrated into gastroenterology training programs; however, its effectiveness remains unclear. We sought to determine whether virtual reality (VR) simulation training can complement and/or replace conventional endoscopy training for novices. Methods: Methodological expectations of Cochrane intervention reviews were followed. Health professions, education and computer databases and conference abstracts were searched until July 2017. We included randomised and quasi-randomised clinical trials comparing VR training to conventional training, no training, or alternative simulation methods. Clinical outcomes were considered, including composite score of competency, procedure completion, time, mucosal visualisation, complication rate, discomfort, global rating of competency. We pooled effect size using random-effects meta-analyses. Results: We identified 18 studies with 421 participants. Ten studies compared VR training with no training, 5 with conventional training, 1 with another form of simulation, and 2 compared VR training methods. Table 1 summarises meta-analyses results. Compared with no training, VR training is beneficial as measured by a priori outcomes. Combined VR and conventional training appears to be beneficial compared to VR training alone. VR curricula grounded in educational theory, such as a progressive learning-based curriculum, provided benefit regarding composite score of competency. Definitive evidence for or against VR training in place of conventional training or another form of simulation is lacking. Conclusion: VR training can effectively supplement early conventional endoscopy training. Comparative effectiveness studies of different simulation modalities are limited. Newer trials provide insight into simulation training approaches grounded in educational theory that improve subsequent clinical performance.